Meteorological Observations at Syowa Station in 1975 by the 16th Japanese Antarctic Research Expedition - Shigenori SAKAI; Shinichi OKIMASA; Shigemi MESHIDA; Takahiro SAKAMOTO (National Institute of Polar Research, 1979)
This paper describes the results of meteorological observations (surface and aerological) at Syowa Station (69°00'S,39°35'E) between 1 February 1975 and 31 January 1976. The main subjects of the observations, the method, and the equipments are the same as in 1974. The data of the surface observations and the aerological observation were immediately reported to World Meteorological Center in Melbourne via Mawson Station, East Antarctica according to the WMO Regulations. The surface meteorological observations and the piball observation were also carried out en route from Syowa Station to Mizuho Station (70°42'S, 44°20'E) and in ice-free areas on the east coast of Lutzow-Holm Bay. Remarkable meteorological features of this year are as follows 1) Temperature in this season was lower than the average, especially monthly mean temperatures for April, July and August were lower than normal year by 2℃ or more. 2) Amount of snow accumulation was larger than that of normal year. 3) Maximum wind speed brought by the severe blizzard at the end of May recorded the highest value ever since Syowa Station was opened.